2013
DOI: 10.1017/s0317167100014281
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery for Large Vestibular Schwannomas: A Canadian Experience

Abstract: The treatment of small to medium sized vestibular schwannomas (VS) with Gamma Knife (GK) stereotactic radiosurgery is a well-documented treatment alternative to surgical resection, with prospective nonrandomized trials demonstrating facial nerve and hearing preservation rates favoring GK over microsurgery 1,2 . Tumor control rates have been described upwards of 94% in recent literature, with acceptable complication rates 3 when compared to microsurgery. Long term actuarial resection-free control rates have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Although radiosurgery has been reported to produce similar facial nerve outcomes for Koos grade 3 tumors (mean volume 9 cm 3 ), its role in the context of large vestibular schwannomas remains controversial and it may be indicated only in patients with minimal symptoms of brainstem compression, surgical contraindications, or significant residual tumor mass despite attempted debulking. 4,15,25,41,43,44,47,50 A proposal to stage large vestibular schwannomas between 2 surgeries has been shown to improve facial nerve outcome and morbidity. 30 Staging the tumor resection was decided intraoperatively if there was cerebellar or The extent of resection is another important factor, with several studies demonstrating significantly lower rates of recurrence with complete or near-complete resections compared with subtotal or partial debulking.…”
Section: Discussionmentioning
confidence: 99%
“…Although radiosurgery has been reported to produce similar facial nerve outcomes for Koos grade 3 tumors (mean volume 9 cm 3 ), its role in the context of large vestibular schwannomas remains controversial and it may be indicated only in patients with minimal symptoms of brainstem compression, surgical contraindications, or significant residual tumor mass despite attempted debulking. 4,15,25,41,43,44,47,50 A proposal to stage large vestibular schwannomas between 2 surgeries has been shown to improve facial nerve outcome and morbidity. 30 Staging the tumor resection was decided intraoperatively if there was cerebellar or The extent of resection is another important factor, with several studies demonstrating significantly lower rates of recurrence with complete or near-complete resections compared with subtotal or partial debulking.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to CK, the median maximal diameter and reported volume for solid and cystic tumors were 3.3 cm and 9.2 cm 3 , compared to 3.3 cm and 8.9 cm 3 , respectively ( Table 1). SRS was delivered in three equal fractions (N=29) over the course of 3 days, to a median prescription dose of 18 Gy (range [18][19][20][21][22][23][24][25] prescribed to median 80% (range 71-M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 90) isodose line (radiobiologically equivalent to a 11.3-Gy single dose, using the linear-quadratic model and α/β ratio of 3 as previously described). 28,36 The cystic tumor of greatest volume was treated with 5 fractions given its still large residual complexity with multiple cystic components after resection.…”
Section: Radiosurgery Treatment Planmentioning
confidence: 99%
“…37 Compilation of the relevant literatures on the outcome of VS of at least Koos Grade III treated by radiosurgery, the overall progression free survival rates range from 82-100% at long-term follow-up (Table 4). 12,29,30,33,[37][38][39][40][41] The available evidence suggested that large VSs are potentially amenable to primary SRS therapy, but there may still be poor tumor control in the largest of tumors. We confirmed this relationship when further stratifying our cohort by volume, with tumors < 15 cm 3 associating with better control rates.…”
Section: Tumor Control: Radiosurgery As An Optionmentioning
confidence: 99%
See 2 more Smart Citations